Concentric Structures and Hydrothermal Venting in the Western Desert, Egypt - Mazzini, Adriano; Lupi, Matteo; Sciarra, Alessandra; Hammed, Mohamed; Schmidt, Susanne T.; Suessenberger, Annette (Frontiers in Earth Science, 2019)
Large-scale concentric structures are enigmatic geological features observed on the Earth surface and on other planetary bodies. Their formation has been attributed to several processes. Here we describe for the first time the results of mapping and characterization of ∼100 large concentric circular structures found in Early Cenomanian argillaceous strata of the Bahariya depression (Egyptian Western Desert). The geological processes that lead to the formation of these features have remained so far elusive. We investigate the concentric structures with a multidisciplinary approach combining field observations, statistical analysis, soil-flux gas measurements and laboratory analyses of rock samples. The whole depression is dissected by the ∼90 km long N60°E-striking dextral strike-slip Bahariya fault. Effusive lavas and shallow intrusions crop out in the down faulted blocks. The mapped circular structures increase in number approaching the fault zone. These features are up to 10 m high and 625 m wide, have a morphology similar in shape to impact craters with steeper external flanks and a gently dipping internal subsided zone. Halite-cemented brecciated sediments from different geological units have been sampled in the central part of the concentric circular structures implying a subsurface mechanism involved in their formation. Petrography analyses revealed also the presence of high- and low-temperature minerals (e.g., Ba-K-feldspars and ferroaluminoceladonite) suggesting former phases of hydrothermal circulation. Soil-gas flux profiles (CO2 and CH4) reveal a modest CO2 increase when crossing the central part of the circular structures inferring enhanced permeability. Field and laboratory data are consistent with a scenario envisaging a diffused and vigorous hydrothermal venting. The proposed scenario includes multiple phases where several geological elements and processes interact. The Bahariya fault, which activity initiated during the Late Cretaceous, provided pathways for Miocene magma ascent toward the surface and for the development of a network of subsurface intrusions in the organic-rich sedimentary rocks of the Bahariya Formation. The interaction of the igneous intrusions with carbon-rich sedimentary deposits produced overpressured fluids, causing the formation of sparse hydrothermal vents at the surface. The elongation of the main axis of the vents and the deformed structures located within the strike-slip zone suggest that faulting controlled the emplacement and the final shape of some of the hydrothermal vents. We speculate that this system may represent a palaeo sediment-hosted hydrothermal system and could be related to the opening of the Red Sea.